Evolution and Efficacy: A Comparative Review of Contemporary Root Canal Filling Materials and Techniques - Manati, Doha Hussein; Manar Ali Hameed (Journal of Science in Medicine and Life, 2025)
Objective: The primary intention is to amalgamate present-day proof (2020–2025) concerning root canal filling materials (gutta-percha variants, carrier cores, resin systems, bioceramic sealers/putties) and techniques (single-cone, lateral compaction, warm vertical/continuous wave, injectable thermoplastic, carrier-based, and hybrid workflows) and to extract practical, evidence-based guidance for clinical decision-making based on the research conducted. Methods: This narrative review with an evidence-based approach combined laboratory studies of high resolution (micro-CT, push-out and leakage assays), animal and ex-vivo biocompatibility experiments, randomized controlled trials, prospective cohorts, and systematic reviews and meta-analyses published from 2020 to 2025. Priority was given to studies that make comparisons of full obturation systems (material + technique), report clinical outcomes of medium to long term, or address retreatability and practical workflow issues. Results: Laboratory studies give consistent evidence that warm thermoplastic methods and perfectly implemented carrier or injectable systems result in lower macroscopic void volumes and better three-dimensional adaptation as opposed to cold lateral compaction. Single-cone procedures together with premixed hydraulic calcium-silicate (bioceramic) sealers generally present similar in-vitro filling measures in circular, instrument-matched canals due to the hydrophilic sealer's ability to fill micro-irregularities and possibly to the generation of mineral similar to apatite over time. In practice, medium-term randomized trials and cohort studies declare no major or consistent superiority of any single material–technique pairing for periapical healing or tooth survival when chemo-mechanical disinfection and coronal restoration are optimized. Among the major practical caveats are differences in product-specific solubility and retrievability (some bioceramic substances can be more difficult to remove), operator reliance on warm techniques, and fluctuating short-term postoperative pain that is linked more to technique execution than to material class. Conclusions: There is not a single obturation material or method that provides better clinical results than others in all cases. The most suitable strategy is to customize the treatment according to the specific case: anatomy, likelihood of retreatment, and the skill level of the operator should be considered when choosing a material- technique system. Bioceramic sealers are able to provide genuine bioactivity and simpler workflows and are thus a strong option for plenty of the normal cases, though the dentists should know the specific product's retreatability and solubility data. Long-term (>5 years) randomized studies and retrievability tests that follow standard procedures are still the challenges for future studies.